空気圧を利用した部分荷重トレッドミル歩行が消費エネルギーに及ぼす影響 - 黒木 裕士; 森永 敏博; 池添 冬芽; 大畑 光司; 家城 弘; 濱 弘道 (理学療法学, 2004)
The purpose of this study was to examine the effect of a new type of treadmill walking on maximum load on the foot, heart rate, and energy expenditure. The walking was performed using the air pressure assisted exercise system that we developed. Five subjects who had received total hip arthroplasty surgery walked at air pressure settings of full bearing (FWB), 2/3 (2/3PWB) and 1/2 (1/2PWB) partial bearing of body weight. When walking at a speed of 1.5-km/h, maximum load on the foot was 105.6% (FWB), 73.0% (2/3 PWB) and 61.0% (1/2 PWB) of body weight. Maximum load (p < 0.001) and oxygen consumption (p < 0.001) decreased significantly at partial weight bearing settings. The results suggest that the subjects walked with a reduced load on the foot and lower energy expenditure when using the air pressure assisted exercise system. 本研究の目的は，空気圧を利用した部分荷重トレッドミル歩行が消費エネルギーに及ぼす影響について検討することである。人工股関節置換術後患者5名を対象に時速1.5kmで全荷重（FWB）歩行，2/3荷重（2/3PWB）および1/2荷重（1/2PWB）設定での歩行を実施したところ，最大足圧はそれぞれ体重値の105.6%（FWB），73.0%（2/3PWB），61.0%（1/2PWB）であり，部分荷重設定で有意に減少した（p < 0.001）。また部分荷重設定で酸素摂取量は有意に減少した（p < 0.001）。このことから本装置では概ね目標とする荷重値を得ながら消費エネルギーを軽減して歩行補助を実現しているものと推察された。